Outdoor learning in the early years : the benefits of outdoor learning in a natural environment - Wilkinson, Rachel, 1982- (2013)
This thesis was completed in the spring of 2013 towards a B.Ed.-degree in teaching from the University of Akureyri. It discusses the concept and benefits of outdoor learning in a natural environment during early childhood. A variety of natural environments and the learning opportunities they provide are explored. Teaching activities for use during outdoor learning sessions in a variety of natural environments, including how to create a natural area within a preschool, are put forth. In today’s society an increasing number of children have become detached from nature and spend less time exploring the world around them. As a result, children are growing up not knowing how to interact with or respect nature. Spending less time outdoors means children are not able to develop their gross motor skills, or get the exercise they need. Outdoor learning allows children to learn in ways that cannot be applied indoors. Outdoor learning provides children with first-hand experience, and an environment where they are free to discover and explore in their own way. Research indicates that learning outdoors benefits many aspects of children’s lives, including their health and wellbeing. Preschools can provide children with the opportunity to learn in and from nature. This can be achieved in a variety of ways, from the Swedish concept of a forest school, to the Czech Republic idea of bringing nature to children. Even a small vegetable garden in an urban preschool provides children with many learning opportunities. Research suggests that children, who learn about nature from a young age, are more likely to respect it during their adult years. This is one of the reasons why it is important for preschools to allow children to interact with nature in various ways. To experience outdoor learning in action and as preparation for the webpage created to coincide with this paper, observations of preschool children during a weekly visit to a forest were made. Observations included how the teachers used the outdoor environment to teach the ...